Comment on “Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Cirrhotic Patients with Acute-on-Chronic Liver Failure” - Weng, Fangbin (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Weng F. Comment on “prognostic value of neutrophil-to-lymphocyte ratio in cirrhotic patients with acute-onchronic liver failure”. Turk J Gastroenterol. 2022;33(3):272.